CARICOM and Belize - the first twenty years. - MC COY, James P. (1993)
Presents a brief review of the forms of integration and the benefits expected by participating developing countries. Evaluates the contribution that membership in the Caribbean integration movement made to economic growth and development in Belize through the 1980s.